Synthesis, characterization, and application of MnFe2O4/FeVO4/modified zeolite nanocomposite as an effective photocatalyst for methylene blue degradation and benzothiophene desulfurization - Shima H. Khabbaz; Ahmad Bagheri; Mehdi Mousavi-Kamazani (Heliyon)
This study details the synthesis of a novel ternary nanocomposite composed of MnFe2O4, FeVO4, and modified zeolite, achieved through a two-step process. The initial step involved the hydrothermal synthesis of the MnFe2O4/FeVO4 composite, followed by its application onto modified zeolite using ultrasonic waves. The synthesized nanocomposite was thoroughly characterized using a range of analytical techniques. X-ray diffraction (XRD) analysis indeed confirmed the successful synthesis of MnFe2O4/FeVO4 composite without impurities and other by-products. This purity was significantly facilitated by the inclusion of hydrazine during the synthesis process. Field emission scanning electron microscopy (FESEM) provided insights into the morphology, indicating that the use of hydrazine resulted in smaller particle sizes and reduced agglomeration. Energy dispersive spectroscopy (EDS) mapping demonstrated a uniform distribution of the particles on the modified zeolite, while transmission electron microscopy (TEM) images revealed spherical particle shapes and the layered structure of the zeolite. Diffusion reflectance spectroscopy (DRS) analysis indicated bandgap values of 1.38 eV for MnFe2O4/FeVO4, 1.48 eV for the 1:1 ratio of MnFe2O4/FeVO4/modified zeolite, and 1.44 eV for the 2:1 ratio. In terms of pollutant degradation, the study evaluated the removal efficiency of methylene blue (MB) across various samples, with the following removal percentages: MnO2/MnFe2O4 (66 %), FeO2/Fe0.5V3.5O8 (60 %), MnFe2O4/FeVO4 (67 %), amorphous (58 %), MnFeO3/Fe2VO4/Mn2V2O7 (64 %), MnFe2O4/FeVO4/modified zeolite (1:1) (84 %), and MnFe2O4/FeVO4/modified zeolite (2:1) (93 %). For sulfur removal, the efficiencies were recorded as 67 %, 28 %, 68 %, 45 %, 22 %, 83 %, and 100 % for the same samples, respectively. This comprehensive characterization and evaluation of pollutant removal efficiencies highlight the potential applications of the synthesized nanocomposite in environmental remediation.